Literature Review: The Role of Green Human Resource Management in Increasing Organization Sustainability - Rizki Maulia, Indah; Yunita, Tyna (Greenation Research & Yayasan Global Resarch National, 2024)
This research is an attempt to find out if Green Human Resource Management (GHRM) currently being implemented in various companies has shown its influence on increasing organization sustainability. This study utilizes a systematic literature review to examine the role of green human resource management (GHRM) in increasing organization sustainability. References used in this systematic literature review study are research papers obtained from Scopus journals Q1, Q2, and Q3. The study showed significant and positive effects of GHRM practices on organization sustainability.